Design and fabricate a gearbox for a given engine specification / Abdul Allim Shah Mohd Sharif and Mohd Faisal Abdul Samad - Mohd Sharif, Abdul Allim Shah; Abdul Samad, Mohd Faisal (1986)
The objective of this project is to design and fabricate a gearbox that can be used in automobiles. This is achieved by carrying out an analytical design based on strength/ wear and durability. The gear ratios are obtained from the dynamic analysis considering tractive effort, resistances, to motion etc. The gear design is based from Lewis Theory and further it is improve by using AGMA Standard Computer is used in the gear design analysis. The language used in the program is Fortran 80. Shaft, splines, synchromesh sleeve and other are designed based on American and British Standards. A model has been made using the results from the analytical finding. Finally the working drawings are prepared.